2013
DOI: 10.1089/scd.2011.0575
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Diverse Signaling Pathways by Ex-Vivo Delivery of Multiple Cytokines for Myocardial Repair

Abstract: We tested the hypothesis that simultaneous transgenic overexpression of a select quartet of growth factors activates diverse signaling pathways for mobilization and participation of various stem/progenitor cells for cardiogenesis in the infarcted heart. Human insulin growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF), stromal cell-derived factor-1 (SDF-1a), and hepatocyte growth factor (HGF) plasmids were synthesized and transfected into skeletal myoblasts (SM) from young male wild-type or tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 45 publications
1
15
0
4
Order By: Relevance
“…One reason for this increased effect is that angiogenic factors facilitate angiogenesis; another reason is that BMSCs can cause massive mobilization and homing of stem cells from peripheral circulation to protect the transplanted stem cells. [29][30][31] Netrins are important in axonal guidance and the regulation and maintenance of central nervous system, and they are also involved in the development of the mammary gland, lung, pancreas and blood vessels. 32 However, recent studies suggested that Netrin-1 functions as a survival factor or pro-angiogenic factor.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this increased effect is that angiogenic factors facilitate angiogenesis; another reason is that BMSCs can cause massive mobilization and homing of stem cells from peripheral circulation to protect the transplanted stem cells. [29][30][31] Netrins are important in axonal guidance and the regulation and maintenance of central nervous system, and they are also involved in the development of the mammary gland, lung, pancreas and blood vessels. 32 However, recent studies suggested that Netrin-1 functions as a survival factor or pro-angiogenic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Приготовление плазмид и трансфекция клеток Плазмиды, кодирующие SDF 1α, HGF, IGF 1, и VEGF, были приготовлены, как описа но в нашей работе [15]. Для трансфекции клет ки были культивированы до 80% 90% конфлю энтности, и по отдельности в каждой из 4 ча шек Петри трансфицированы каждой из 4 плазмид (IGF 1, VEGF, SDF 1α, или HGF), ис пользуя катионный вектор Lipofectamine 2000 (Invitrogen).…”
Section: материалы и методыunclassified
“…Методы анализа миграции клеток и спо собности клеток к ангиогенезу in vitro Кондиционная среда (CM) от TransSM и NatSM была использована для анализа мигра ции клеток HUVEC, методом транслуночной миграции (in vitro transwell migration system), как было описано нами ранее [15]. Для анализа способности к ангиогенезу клеток HUVEC in vitro использовался метод формирования мик ротрубок (tube formation assay) [15].…”
Section: материалы и методыunclassified
See 2 more Smart Citations